2010
DOI: 10.1523/jneurosci.0983-10.2010
|View full text |Cite
|
Sign up to set email alerts
|

The Postsynaptic Adenomatous Polyposis Coli (APC) Multiprotein Complex Is Required for Localizing Neuroligin and Neurexin to Neuronal Nicotinic Synapsesin Vivo

Abstract: Synaptic efficacy requires that presynaptic and postsynaptic specializations align precisely and mature coordinately. The underlying mechanisms are poorly understood, however. We propose that adenomatous polyposis coli protein (APC) is a key coordinator of presynaptic and postsynaptic maturation. APC organizes a multiprotein complex that directs nicotinic acetylcholine receptor (nAChR) localization at postsynaptic sites in avian ciliary ganglion neurons in vivo. We hypothesize that the APC complex also provide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 70 publications
0
21
0
Order By: Relevance
“…Mutations in ARX, FOXG1, and TSC1/2 are predicted to affect β-catenin/Wnt signaling levels and to cause changes in neuronal migration and maturation (Mak BC et al 2003; Seufert DW et al 2005; Danesin C et al 2009). MAGI-2/S-SCAM, a synaptic scaffold protein, binds directly to β-catenin and different S-SCAM isoforms are involved in both excitatory and inhibitory synapse assembly (Nishimura W et al 2002; Hirabayashi S et al 2004; Sumita K et al 2007; Rosenberg MM et al 2010). Lis1 binds directly to APC (Orlova KA and PB Crino 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Mutations in ARX, FOXG1, and TSC1/2 are predicted to affect β-catenin/Wnt signaling levels and to cause changes in neuronal migration and maturation (Mak BC et al 2003; Seufert DW et al 2005; Danesin C et al 2009). MAGI-2/S-SCAM, a synaptic scaffold protein, binds directly to β-catenin and different S-SCAM isoforms are involved in both excitatory and inhibitory synapse assembly (Nishimura W et al 2002; Hirabayashi S et al 2004; Sumita K et al 2007; Rosenberg MM et al 2010). Lis1 binds directly to APC (Orlova KA and PB Crino 2010).…”
Section: Discussionmentioning
confidence: 99%
“…The synaptic scaffolding molecule (S-SCAM; [49]) is also present and interacts with NLGN2 at inhibitory synapses [50]. Furthermore, it was demonstrated that in chicken, where only three forms of NLGN is present (NLGN1,3,4) and NLGN2 is absent [51], S-SCAM is directly associated with NLGN1 at cholinergic synapses of the ciliary ganglion [52]. In these synapses, S-SCAM indirectly interacts with the adenomatous polyposis coli protein that organizes a multimolecular protein complex which targets α3 nicotinic ACh receptors to the postsynaptic membrane [53], [54].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, several MAGUKs were found to localize to neuronal nicotinic synapses with neuroligin 1 (NL1). S-SCAM, PSD-93, and PSD-95 are all enriched at synapses containing nicotinic acetylcholine receptors (nAChRs), and all 3 can bind to NL1; however, only S-SCAM influences the surface expression of NL1 (Rosenberg and others 2010). S-SCAM links NL1 to the postsynaptic adenomatous polyposis coli (APC) complex via β-catenin.…”
Section: Maguk Interactions With Cell Adhesion Molecules During Develmentioning
confidence: 99%
“…S-SCAM links NL1 to the postsynaptic adenomatous polyposis coli (APC) complex via β-catenin. NL1 binds to both the PDZ1 and WW domains of S-SCAM, and β-catenin associates with its PDZ5 domain (reviewed in Rosenberg and others 2010). The APC complex interacts with nAChRs, via the protein 14-3-3, and with cytoskeletal proteins.…”
Section: Maguk Interactions With Cell Adhesion Molecules During Develmentioning
confidence: 99%
See 1 more Smart Citation